Preparation of Nitrogen Slow Release fertilizer by the inclusion of commercial Urea with Syrian Zeolite Ore and testing it agronomically - يونس سليمان; ليلى حبيب (Latakia University Journal -Biological Sciences Series, 2025)
A slow release fertilizer (SRF) prepared by the inclusion of conventional commercial urea with zeolite ore, and the use of maize starch as adhesive, the components ratio were 5:1:1 for zeolite: urea: starch. The prepared SRF tested agriculturally by Tritical crop )Triticosecale wittmack (grown in pot experiment in greenhouse at Tishreen university. Five rates of Nitrogen were applied in addition to Control with no added N-fertilizer, these rate were 100, 200, 300, 400, 600 kg N/Ha, tow sources of Nitrogen fertilizer were used: commercial urea and the prepared SRF. Three cuts were carried out on the growing triticale plant, and dry weight was recorded. Nitrogen concentration and uptake from plant measured during growing period. Nitrogen use efficiency was determined by the calculation of Apparent Recovery Efficiency ARE%. The main achieved results: SRF produce more dry matter weight compared to urea when low rates of nitrogen were applied (200-300 kg N/Ha), with un increase percentage of 9 and 16% respectively compared to commercial urea. When high rate of fertilizers were applied (400- 600 kg N/Ha), urea treatment produced more dry matter yield compared to SRF in first cut, whereas this difference disappeared in the second cut. In third cut SRF dry matter yield production exceed that produced by urea when 400 and 600 kgN/Ha were applied, with an increase of 49 and 28%respectively. There was an apparent increase in Nitrogen concentration and uptake from shoots when SRF was applied. SRF realized more Nitrogen use efficiency compared to commercial urea.